ENTERPRENEUR TERHADAP KINERJA UKM DI KOTA MEDAN - Maya Sari (Jurnal Riset AKuntansi dan Bisnis, 2014)
Development will be more successful if it is supported by enterpreneurs who can create jobs because the government is very limited capabilities. UKM in the city of Medan is an industry that still exist because this field of activities is not affected by the crisis. Increase in units small and medium enterprises can not be separated from the role of enterpreneurial UKM. So in this study, the authors raised the title "Enterpreneur Effect on Performance of UKM in Medan". The purpose of this research is to examine and analyze the effect of the enterpreneur to the performance of UKM. in the city of Medan.This research uses census approach to small and medium enterprises in the city of Medan. This type of research is  descriptive quantitative research is to test and mnganalisis Enterpreneur Effect on Performance of SMEs in the city of Medan. Statistical tools used to analyze the hypothesis is a simple linear regression analysis.The results from this research is the influence of enterpreneurs on the performance of UKM in the city of Medan. The research concludes that there are positive correlation between the entrepeneur to the performance of UKM.